Необходимость, сценарии и варианты реформирования российского научного комплекса - Семенов, Евгений (Вопросы государственного и муниципального управления, 2007)
The collapse of the Soviet administrative system and the break-up of the Soviet Union brought about the considerable changes within the Russian academic community. Now it is perfectly evident that it was absolutely unprepared for the new market environment. The Russian science turned out to be almost unable to adapt to and develop in the new environment. Thus, as a result, for the last fifteen years it has been witnessing a rapid systemic deterioration, which is often characterized as a crisis or catastrophe. A decline of the Russian academic community is mistakenly explained by a lack of funding. But, actually, there exist a systemic crisis, where a lack of funding results from the more important underlying reasons. The thorniest aspect of the problem is that the historically aggravated situation makes it impossible to carry out the reform of the Russian science for the last fifteen years, though the reform is vital for the country and the science itself. There are two social powers, knowing exactly what they want, in present-day Russia. These are officials and businessmen. Of course, there are rudiments of civil society, but, unfortunately, it serves as a background for these historical characters, rather than acts as an independent actor of the drama. The scientific scene is identical. There are government officials and businessmen, having their own interests and views on scientific and technical development. Also, there are academic aristocrats and bureaucrats (calling themselves as “academic elite” or “elite of the academic community”), who, in fact, represent nomenclature class, having their own particular interests. And, lastly, there is an academic community, not the “elite”, but the academic community proper, which encompasses scholars and academics who conduct scientific researches. It should be noted that the mentioned groups express rather diverse and contradictory interests. There may be distinguished four shaped trends of science development in Russia. They reflect the standpoints of the major social forces, which have a particular interest and take a sensible position on fundamental science and emphasize either preserving, or using and developing a scientific potential. The understanding of the essence of the science management differs greatly within these social forces, with the emphasis laid on either the idea of science monopolization, or controllability, or self-organization. For a forward-looking state policy on fundamental science formulation it is essential to combine the idea of controllability and self-organization, i.e. it is crucial to achieve and constantly maintain the optimum balance between government control over science and self-organization of the academic community with active business participation. This implies emergence of a competitive environment and setting out its behaviour rules; establishment of a system of competitive selection of projects and programs; setting up independent expert commissions; introducing a project form of the fundamental research organization; defining state’s and science’s priorities; and overcoming isolation of the separate aspects of fundamental science. With seemingly considerable diversity of options, in fact, there are four feasible scenarios of science development in Russia: inertial (sluggish), revolutionary, radical reformatory and evolutional reformatory. The inertialscenario, though there are some options, implies preserving the basics of the existing organization in research and development area, the mechanisms of controlling and funding scientific researches. The revolutionaryscenario is quite the opposite to the inertial one (scenario of preservation) and offers to substitute the obsolete national system of science with a new one, built up not basing on the old system, but parallel to it. The revolutionary option is based on the assumption that the Russian academic community, first of all the Russian Academy of Sciences, is impossible to reform. The radicalreformatory scenario involves transferring of fundamental science potential to the consumer, interested in its use and development, – higher school, innovation structures, a set of governmental departments. This option encourages the establishment of an efficient mechanism of coordinating all the aspects of fundamental science at the state (government) level. The evolutionalreformatory scenario provides for a qualitative change and strengthening of both government control over fundamental science and selfcontrol of the academic community. The evolutional reformatory scenario is considered the best as applicable for present-day Russia. It proposes sensible swift actions and has a set of definite advantages, as follows: consideration of the Russian cultural and historical raditions, due to the fact that historically science in Russia developed and shaped as a “state business”; consideration of the basics of contemporary world’s and Russia’s peculiarities, which imply a change of organizational forms of fundamental science, complying with competitive market environment; consideration of contemporary short-term conditions and factors in Russia, first of all – the compliance of the changes being carried out in the organization of fundamental science with the strengthening of the state; retaining of the competent and prolific part of the academic community and the development of the advanced and efficient forms of project and program organization of fundamental researches; budget support focusing on the most advanced and qualified scientific potential, which is in high demand due to competitions, independent expert commissions and government order; elimination of nomenclature and corporate management by a considerable part of fundamental science potential, which made it impossible to implement any reform of the fundamental research organization for the last fifteen years in Russia.